2001
DOI: 10.1007/s001980170079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormonal Replacement Therapy on Bone Metabolism in Young Adults with Beta-thalassemia Major

Abstract: The aim of our cross-sectional study was to evaluate the effects of hormonal replacement therapy (HRT) on a population of young thalassemics in order to understand better the role of hypogonadism in the balance of bone metabolism. Markers of bone turnover and bone mineral density (BMD) were measured in 40 young patients (mean age 19.8 +/- 4.5 years) with beta-thalassemia major: 20 subjects were biochemically eugonadal. since they were undergoing HRT (group A, treated patients), and 20 were hypogonadic, having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 32 publications
(30 reference statements)
9
52
1
8
Order By: Relevance
“…This suggests that an important determinant of the often suboptimal bone response to testosterone replacement reported previously may be inadequate prior testosterone treatment, largely due to the pharmacological limitations and inconvenience of the available testosterone products. Our findings on the bone density benefits of sustained, adequate treatment are consistent with findings that AD thalassaemic adolescents taking regular testosterone treatment had higher BMD than others whose testosterone treatment was irregular (42,43). In most previous longer (.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that an important determinant of the often suboptimal bone response to testosterone replacement reported previously may be inadequate prior testosterone treatment, largely due to the pharmacological limitations and inconvenience of the available testosterone products. Our findings on the bone density benefits of sustained, adequate treatment are consistent with findings that AD thalassaemic adolescents taking regular testosterone treatment had higher BMD than others whose testosterone treatment was irregular (42,43). In most previous longer (.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, iron chelation has correlated with growth failure and bone abnormalities, and high desferrioxamine dosage has been associated with cartilage alterations (5,6). More puzzling, however, is the observation that, despite the normalization of haemoglobin levels, adequate hormone replacement, and effective iron chelation, patients continue to show an unbalanced bone turnover with an increased resorptive phase resulting in seriously diminished bone mineral density (BMD) (7,8).…”
Section: Thalassaemia and Bone Diseasementioning
confidence: 99%
“…In the absence of vertebral compression (crush) fractures, the diagnosis of osteoporosis is indicated by the presence of both a clinically significant fracture history and BMD Z-score less than or equal to -2.0 SD (22). In some studies (23,24), in order to reduce the u n c o r r e c t e d p r o o f influence of bone size on BMD measurements in the growing skeleton, the apparent volumetric density of the lumbar spine has been calculated using a specific formula (25). In TM patients, it is very common to find low BMD values (osteopenia or osteoporosis) and in some studies up to 90%, even in optimally transfused and chelated patients, as is shown in Table 1 (7,(26)(27)(28)(29)(30)(31).…”
Section: Bone Metabolism In Tm Patientsmentioning
confidence: 99%
“…Vertebral fractures are usually underestimated, and their prevalence varies from 2.6% to 13% (27,36). TM patients, in spite of following a regular transfusional regimen, and receiving adequate sex hormone replacement and chelating therapy, show imbalanced bone turnover with an increased resorptive phase that is not followed by an appropriate neoformation rate, resulting in a decreased BMD, particularly at the vertebral level, where trabecular bone is mostly represented (23,27,(37)(38)(39). In previous studies (14,23), we described a decreased neoformation phase in accordance with Mahachoklertwattana (24) and histomorphometric studies performed by De Vernejoul (40).…”
Section: Bone Metabolism In Tm Patientsmentioning
confidence: 99%
See 1 more Smart Citation